The Shifting in the Legal Politics of Regulating the General Principles of Good Governance in Indonesian Legislation - Fauzani, Muhammad Addi (Universitas Islam Negeri Raden Intan Lampung, 2023)
Prior to the enactment of Law Number 30 of 2014 concerning Government Administration, the regulation of the General Principles of Good Governance (AAUPB) was abstract in nature. With the explicit mention of AAUPB in this new Administrative Law, it is intriguing to examine it from a legal and political perspective and consider its legal consequences. This article aims to analyse the form legal political shift in the regulation of AAUPB in Indonesia and the resulting legal consequences. This study is normative juridical research using a legislative approach. The findings reveal that, first, the shift in the legal politics of AAUPB in Indonesia occurred with the issuance of Law Number 30 of 2014 concerning Government Administration. The Law Number 30 of 2014 concerning Government Administration shifted the legal politics of AAUPB, as there is a normativization in the form of AAUPB regulation in the article. Secondly, the legal consequences of the shift in the legal politics of AAUPB in Indonesia are as follows: a) the status of the principle becomes a concrete legal norm; b) it facilitates courts in judging an action of administrative officials; c) it eases the control of administrative actions; d) it simplifies public control; e) it emphasises the need for supervision of official actions; f) it guarantees civil rights through the enforcement of AAUPB; g) it prevents governmental arbitrariness.